Production, Promotion, and Operational Costs and Their Effects on Profitability: Indonesian Food and Beverage Sector Analysis - Kemuning, Linggar Sekar; Raharjo, Teguh Budi; Fajri, Aminul (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to determine the Effect of Production Costs, Promotion Costs, Operational Costs and Sales Volume on Net Profit (Empirical Study on Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2024). Research Design and Methodology: This study is a descriptive study with a quantitative approach. The population in this study is the Food and Beverage Sub-Sector Manufacturing Companies listed on the IDX for 5 periods (2020-2024). The total population is 128 companies, the selection of the research population was carried out using the purposive sampling method and obtained 64 companies, resulting in a sample of 320 companies. The analysis method used in this study is a multiple regression model with the SPSS version 22 program. Findings and Discussion: The results of this study indicate that Production Costs, Promotion Costs, and Sales Volume have an effect on Profit, while Operational Costs do not affect net profit in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2020-2024. Implications: These findings highlight the limited predictive power of certain financial ratios in the technology sector and the conditional role of profitability. Future research should include broader indicators or sector-specific dynamics to improve understanding and guide investment or policy decisions